Islamic Republic of Afghanistan : Technical Assistance Report-Report on External Sector Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2020)
This technical advice provided by the staff of the IMF to the authorities of Afghanistan in response to their request for technical assistance (TA). The mission objectives were to assist the Da Afghanistan Bank (DAB) in improving the quality of the balance of payments and international investment position (IIP) statistics. The mission took stock of recent improvements in the ESS compilation practices and commended the DAB's Monetary Policy Department (MPD) for achieving most of the 2018 TA recommendations. Despite the progress achieved, major shortcomings remain to be addressed to enhance the policy relevance of external sector statistics (ESS) data. The highest priority should be given to the improvement of personal transfer's coverage and the estimation of unrecorded personal transfers. Remittances through autonomous Money Service Providers and informal channels are not captured; although, there seems to be a large remittance channel. The inclusion of the opium economy will have significant impact in the national and international accounts.